Hydration status, neuromuscular responses, and competitive state anxiety in professional tennis player during official competition - Lopez-Samanes, A.; Ortega, J. F.; Pérez-López, A.; Pallarés, J. G.; Mora-Rodriguez, R. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Tennis is a racquet sport with thousands of followers around the world. During non-official competition, physiological and psychological variables have been studied. Data from the hydration status (Hornery et al., 2007) indicates that tennis players compete hypohydrated but does not sustain important dehydration during a match. Likewise, neuromuscular fatigue has not been evidenced after a tennis match (Ojala & Hakkinen, 2013). In addition, before a match, competitive state anxiety (CSA) showed changes in somatic and cognitive anxiety (Filaire et al., 2009). On the other hand, during official competition (ATP/WTA, Challenger and Futures), professional players are awarded with prize money/points for the ATP ranking, which could be associated with higher physiological demands and increased competitive anxiety. The aim of this study is to describe hydration status, neuromuscular responses, and CSA in professional tennis player during an official competition. Methods: During the qualifying draw from a 10000 dollar ITF Future tournament, 9 professional male tennis players (3 with ATP ranking between1400-1800 and 6 between 50-180 in the national ranking) were assessed using, a battery of physiological and psychological measurements. Before the match, hydration status was assessed by urinary specific gravity (USG), and fluid balance was assessed by pre and post-match body weight changes. Before, and after match, neuromuscular fatigue was assessed by counter movement jump (CMJ) and competitive state anxiety was measured using a validated questionnaire (CSAI-2R). Results: USG before the match was 1.026±0.002. After the match participants lost 1.2±0.2% of their body weight. CMJ decreased a 4.85±1.4% after match no reaching statistical significance (p=0.203). Before match, CSA scores for somatic and cognitive anxiety indicated medium to lower values. Discussion: As it was described in non-official matches, professional tennis players began official matches in a hypohydrated status. However the beverages ingestion during the match avoided significant dehydration and there were no evidence of neuromuscular fatigue. Our findings suggest that in spite of the special considerations that an official tennis match represents, CSA profile is lower in comparison to a non-official competition.